A Decade of Literature on Climate in Phytopathological Research: Visualising and Bibliometrics Analysis. Issue 1 (1st November 2022) - Muhammad, M; Zawawi, M A M; Jusoh, M F; Naher, L; Latif, N S A; Hasli, M A
Abstract : Climate change is a global concern which is predicted to dominate phytopathological research. Hence, we performed a bibliometric analysis of climate changes in relation to plant pathology research from 2012 to 2022, in order, to ascertain the publication trend in this study field. Consequently, Web of Science (WoS), a well-known database was chosen to obtain a total of 335 articles that matched the inclusion criteria. This research attempts to expand graphical mapping of the bibliographic information using VOSviewer software. The research conducted the performance and network mapping approaches: publication trends, subject area, most active journals and countries, citation metrics, highly cited papers, co-authorship, and co-occurrence of the keywords. Our analysis essentially concludes that the last decade of scientific papers shows a positive tendency of climatic influence on the plant pathology research field. Our work can be used by plant pathologists to consider the future direction of disease detection in light of global warming and soil status.